2013
DOI: 10.3130/aija.78.625
|View full text |Cite
|
Sign up to set email alerts
|

Study on Visual Complexity Using RMS Contrast Statistics in Streetscape Composition in Algeria and Japan

Abstract: This study aims to explore visual complexity in streetscape composition using a new method of measurement based on RMS contrast information. The dataset was composed of 74 streetscape images, taken in Algeria and Japan in daytime and nighttime. The evaluation and analysis covered two phases: (1) the subjective quantification of visual complexity using factor analysis and ranking method. (2) The visual complexity measurement based on RMS contrast statistics of streetscape images. The results showed a positive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Maki (1988) discussed the collage-like surface in Japan and the ways that infrastructures such as signs and vending machines shape the image of the urban space. Kacha Epe Mansouri et al (2013) compared the streetscape composition in Algeria and Japan, revealed the positive correlations between visual complexity and streetscape images according to individuals' cognition. Ohno (2016) claimed that the Japanese city, no matter large or small, tends to resemble an archipelago-like structure with huge blocks and buildings as "island" and the other place nearby as "sea".…”
Section: Introductionmentioning
confidence: 99%
“…Maki (1988) discussed the collage-like surface in Japan and the ways that infrastructures such as signs and vending machines shape the image of the urban space. Kacha Epe Mansouri et al (2013) compared the streetscape composition in Algeria and Japan, revealed the positive correlations between visual complexity and streetscape images according to individuals' cognition. Ohno (2016) claimed that the Japanese city, no matter large or small, tends to resemble an archipelago-like structure with huge blocks and buildings as "island" and the other place nearby as "sea".…”
Section: Introductionmentioning
confidence: 99%